Systemic Racism in Communication Sciences and Disorders Academic Programs: A Commentary on Trends in Racial Representation. - Whitfield, Jason A. (American Journal of Speech-Language Pathology, 2023)
Purpose: As a discipline, communication sciences and disorders (CSD) has struggled to address equity and inclusion for students, professionals, and scholars from historically excluded racial groups. Recent publications in this periodical that have begun to confront systemic racism in the discipline have been met with some expected resistance. In this commentary, I attempt to support and expand an argument made by Ellis and Kendall (2021), namely, that systemic racism has been and continues to be a normal and persistent feature of our academic programs. A comparison to U.S. Census data suggests that Asian, Black, Indigenous, Native, Latino/a/e, and multiracial CSD professionals are represented to a drastically lower rate compared with their representation in the population at large. Furthermore, publicly available data summaries indicate that there is a reduction in the level of racial diversity that is associated with an increase in White representation across the entire progression of the professional training and certification process, with the greatest level of diversity at the undergraduate level followed by the graduate and professional levels. Conclusions: A general knowledge of social and legal history in the United States would suggest that the relative reduction in representation across the academic and professional levels of the CSD disciplines results from policy and practice patterns that serve to preserve a White-dominant culture in our profession and exclude People of Color. Continued efforts broadly based in critical race studies may prove as a useful tool to identify, confront, and transform current policy and practice patterns in our national organization, academic programs, and accrediting bodies that have produced and sustained levels of inequality and White dominance in our programs and disciplines.